Association of 1, 5-Anhydroglucitol with Diabetes and Microvascular Conditions. (1st November 2014) - Selvin, Elizabeth; Rawlings, Andreea M; Grams, Morgan; Klein, Ronald; Steffes, Michael; Coresh, Josef
Abstract: BACKGROUND: 1, 5-Anhydroglucitol (1, 5-AG) is inversely related to hyperglycemia and may be a useful indicator of short-term (1–2 weeks) hyperglycemia and glycemic excursions, but its prognostic value is unclear. We sought to evaluate the associations of 1, 5-AG with risk of diabetes and microvascular disease. METHODS: We measured 1, 5-AG in blood samples from over 10 000 participants in the ARIC (Atherosclerosis Risk in Communities) Study (baseline, 1990–1992) and characterized the independent associations with prevalent retinopathy and with incident chronic kidney disease and incident diabetes during approximately 20 years of follow-up. RESULTS: We found that 1, 5-AG was associated with prevalent retinopathy, driven primarily by the strong association in persons with diagnosed diabetes: adjusted odds ratio (OR) 11.26 (95% CI, 6.17–20.53) for <6 μg/mL compared to 1, 5-AG ≥10 μg/mL. This result remained significant after further adjustment for hemoglobin A1c (Hb A1c ) (OR, 4.85; 95% CI, 2.42–9.74). In persons with diagnosed diabetes, low 1, 5-AG (<6 μg/mL vs ≥10 μg/mL) was also associated with a >2-fold increased risk of incident chronic kidney disease [adjusted hazard ratio (HR), 2.83; 95% CI, 2.15–3.74] and remained significant after adjustment for Hb A1c (HR, 1.43; 95% CI, 1.02–2.00). Nondiabetic participants with high 1, 5-AG (≥10 μg/mL) had the lowest prevalence of retinopathy and lowest risk of kidney disease. In persons without diagnosed diabetes at baseline, 1, 5-AG <10 μg/mL was also associated with incident diabetes (adjusted HR, 2.29; 95% CI, 2.03–2.58). CONCLUSIONS: 1, 5-AG was associated with long-term risk of important microvascular outcomes, particularly in persons with diagnosed diabetes and even after adjustment for Hb A1c . Our results suggest 1, 5-AG may capture risk information associated with hyperglycemic excursions.